A Cloud-Structured Fractal Multiband Antenna for 4G/5G/WLAN/Bluetooth Applications - Zhen Yu; Guodong Zhang; Xiaoying Ran; Ziheng Lin; Yao Li (International Journal of Antennas and Propagation)
This study proposes a multiband printed planar antenna with cloud-like grooves. The outer contour of the antenna is shaped like a cloud, and the groove-like pattern is similar to the cloud-like pattern in ancient China. It can support 3G, 4G, 5G, WLAN, Bluetooth, WiMAX, and other applications. Based on the traditional monopole antenna, the antenna combines the advantages of a coplanar waveguide. The antenna uses an Archimedes helix to create grooves that resemble ancient Chinese cloud structures. Three effective frequency bands are obtained. The relative bandwidth of the first frequency band (1.8–2.6 GHz) is 32.7%, covering 5G band n2 (1.85 GHz–1.99 GHz), WCDMA (1.9–2.17 GHz), LTE33-41 (1.9–2.69 GHz), Bluetooth (2.4–2.48 GHz), WLAN (2.4–2.48 GHz), LTE Band40 (2.3–2.4 GHz), ISM Band (2.42–2.4835 GHz), WiMAX (2.3 GHz), and SCDMA (1.88–2.025 GHz and 2.3–2.4 GHz). The second frequency band (3.35–4.1 GHz) has a relative bandwidth of 20.5%, covering LTE42/43 (3.4–3.8 GHz) and 5G band n78 (3.4 GHz–3.8 GHz). The relative bandwidth of the third band (5.5–7.9 GHz) is 40.3%, covering Emergency and Public Protection (5.85 GHz–5.925 GHz) (WRC03). The antenna is printed on a G10/FR4 dielectric board with a size of 1.6∗45∗40 mm3, the dielectric constant is 4.4, and the omnidirectional radiation pattern gain is 0.59–4.14 dBi. The measurement results are in good agreement with the simulation results. The proposed design method is verified to meet the requirements of various wireless applications.